Fungal root endophytes influence plants in a species‐specific manner that depends on plant's growth stage. (25th January 2021) - Geisen, Stefan; ten Hooven, Freddy C.; Kostenko, Olga; Snoek, L. Basten; van der Putten, Wim H.
Abstract: The mycobiome (fungal microbiome) influences plants—from seed germination to full maturation. While many studies on fungal‐plant interaction studies have focused on known mutualistic and pathogenic fungi, the functional role of ubiquitous endophytic fungi remains little explored. We examined how root‐inhabiting fungi (endophytes) influence range‐expanding plant species. We isolated endophytes from three European intra‐continental range‐expanders and three congenerics that are native both in the range expander's original (southern Europe) and new (northern Europe) range. To standardize our collection, endophytes were obtained from all six plant species growing under controlled conditions in northern (new range of the range expander) and southern (native range of the range expander) soils. We cultivated, molecularly identified and tested the effects of all isolates on seed germination, and growth of seedlings and older plants. Most of the 34 isolates could not be functionally characterized based on their taxonomic identity and literature information on functions. Endophytes affected plant growth in a plant species–endophyte‐specific manner, but overall differed between range‐expanders and natives. While endophytes reduced germination and growth of range‐expanders compared to natives, they reduced seedling growth of natives more than of range‐expanders. Synthesis . We conclude that endophytic fungi have a direct effect on plant growth in a plant growth stage‐dependent manner. While these effects differed between range expanders and natives, the effect strength and significance varied among the plant genera included in the present study. Nevertheless, endophytes likely influence the establishment of newly arriving plants and influence vegetation dynamics. Abstract : We conclude that endophytic fungi have a direct effect on plant growth in a plant growth stage‐dependent manner. While these effects differed between range expanders and natives, the effect strength and significance varied among the plant genera included in the present study. Nevertheless, endophytes likely influence the establishment of newly arriving plants and influence vegetation dynamics